Cell Church: Its Situation in British Evangelical Culture - Harvey, David (Journal of contemporary religion, 2003)
The rise of the cell church model in British churches since the 1990s has been noted not just by church growth enthusiasts, but also by the wider ecclesiastical world. This paper provides a preliminary examination of the background, status, and characteristics of cell churches. It links the rise of the phenomenon to the church growth movement and to the current trend of rationalisation in society. Using recent written material and interviews with cell church leaders, the author places cell church in the continuum of evangelical 'experiences'. From a sociological point of view, Ritzer's 'McDonaldization' model is used to show how a rationalised structure can exert considerable control on its members.